Sikap Nasionalisme Masyarakat Perbatasan Kecamatan Entikong Kabupaten Sanggau - Lestari, Ayu; Zakso, Amrazi; Atmaja, Thomy Sastra (Journal of Civic Education, 2024)
This study examines the nationalism attitudes of border communities in Entikong District, Sanggau Regency, Indonesia. Nationalism is understood as a sense of love and dedication to one’s homeland, demonstrated through a willingness to contribute to the nation's progress and prosperity. Employing a qualitative research design with a descriptive approach, the study involved continuous engagement with individuals and groups in the community. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings reveal that the nationalism of the Entikong border community is strong. This is evidenced by their enthusiastic and responsible display of the Indonesian flag during independence celebrations, compliance with border regulations, preference for domestic products, and active participation in community activities such as mutual cooperation and events marking the country's independence. The community also exhibits a commitment to fostering religious harmony and prioritizing locally made goods. However, the study is limited in scope as it does not explore other factors influencing nationalism, such as the role of mass media, educational initiatives, or government policies. Future research should delve deeper into these aspects to provide a more comprehensive understanding of the drivers of nationalist attitudes in border regions.